Igneous Activity, Tectonics, And Hydrothermal Precious-Metal Mineralization In The Great Basin During Cenozoic Time - Miles L. Silberman (Society for Mining, Metallurgy & Exploration, 1976)
Three major suites of igneous rocks were erupted in the Great Basin in middle and late Cenozoic time. The first, most likely, resulted from sub- duction of a Pacific plate (Farallon plate) beneath the North American plate, resulting in eruption of andesitic rocks in the northern Great Basin between 42 and 43 m.y. ago. Between 34 and 17 m.y. ago, igneous activity migrated to the southwest, largely as eruption of volumincus rhyolite-quartz latite ash-flow sheets, ending about 17 a.y. ago with the onset of crustal extension and north-south-trending Basin and Range (rift) faulting. The second volcanic suite erupted between 17 and 8 m.y. ago in the northern Great Basin; is mostly basaltic or bimodal basalt-rhyolite. The third volcanic suite consists of andesitic and rhyolitic lavas and some basalt erupted between about 22 to 6 m.y. ago in the western Great Basin along the northwest-trending Walker Lane fault zone. Hydrothermal ore deposits are associated with all suites of igneous rocks, but the largest production has come from mines associated with andesitic rocks of the third (western Great Basin) suite. The oldest (34 to 42 m.y.) andesitic rocks (first suite) of the northern Great Basin have produced some large deposits; slightly younger silicic rocks of this suite are mostly barren. Many small ore deposits are associated with the 17- to 8-m.y.-old basalts (second suite) of northern Nevada.